Climate change adaptation : beyond greening humanitarian response - Cook, Alistair David Blair (Nanyang Technological University, 2021)
Humanitarian response traditionally provides immediate relief and protection to a population affected by conflict and/or natural disaster. While humanitarian action stays true to its primary mandate, environment considerations in general, and specifically climate change adaptation, have yet to take root and be integrated into humanitarian action frameworks. The worrying trend of increasing frequency and severity of climate-induced disaster events in recent years provides all the more reason for humanitarian response to be more sensitive and attentive to climate change adaptation efforts. After all, the Sendai Framework for Disaster Risk Reduction 2015-2030 calls for “enhancing disaster preparedness for effective response and to “Build Back Better” in recovery, rehabilitation and reconstruction”.3 This sets the tone for humanitarian action to look beyond short-term relief and take an active role in building the climate resilience of the affected communities.